Evolving the "How Might We?" Tool to Include Planetary Boundaries. (May 2022) - Vignoli, M.; Roversi, S.; Jatwani, C.; Tiriduzzi, M.; Finocckì, C.
Abstract: This work aims to study the evolution of the "Human and planet balance tool" as part of Prosperity Thinking. Prosperity Thinking is a sustainable design methodology that takes into account human and planet means. Through a literature review on sustainable design, we noticed that there is a lack of methods that take into account the problem definition stage. We developed a "Human and planet balance tool" which helps framing sustainable design challenges. Results show that designers, innovators, and changemakers have an interest in a methodology to analyze and address systemic challenges.